The greenhouse gas abatement potential of productivity improving measures applied to cattle systems in a developing region - Salmon, Gareth R.; Marshall, Karen; Tebug, Stanly Fon; Missohou, Ayao; Robinson, Timothy P.; Macleod, M. (Elsevier, 2018)
Developing countries are experiencing an increase in total demand for livestock commodities, as populations and per capita demands increase. Increased production is therefore required to meet this demand and maintain food security. Production increases will lead to proportionate increases in greenhouse gas (GHG) emissions unless offset by reductions in the emissions intensity (Ei) (i.e. the amount of GHG emitted per kg of commodity produced) of livestock production. It is therefore important to identify measures that can increase production whilst reducing Ei cost-effectively. This paper seeks to do this for smallholder agro-pastoral cattle systems in Senegal; ranging from low input to semi-intensified, they are representative of a large proportion of the national cattle production. Specifically, it identifies a shortlist of mitigation measures with potential for application to the various herd systems and estimates their GHG emissions abatement potential (using the Global Livestock Environmental Assessment Model) and cost-effectiveness. Limitations and future requirements are identified and discussed. This paper demonstrates that the Ei of meat and milk from livestock systems in a developing region can be reduced through measures that would also benefit food security, many of which are likely to be cost-beneficial. The ability to make such quantification can assist future sustainable development efforts.